Developing Indigenous Church Music in the Kalahan Society - Rice, Delbert (Silliman Journal, 2024)
This paper describes an experiment to develop indigenous church music for a Philippine cultural minority—the Kalahan of North Luzon. The author has found that certain types of Kalahan music can be utilized to express Christian concepts—and that the development of indigenous church music is possible in the Philippines.